2015
DOI: 10.1007/s00360-015-0894-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response in liver and Brockmann bodies of rainbow trout to inhibition of lipolysis; possible involvement of the hypothalamus–pituitary–interrenal (HPI) axis

Abstract: We previously demonstrated in rainbow trout that the decrease in circulating levels of fatty acid (FA) induced by treating fish with SDZ WAG 994 (SDZ) induced a counter-regulatory response in which the activation of the hypothalamus-pituitary-interrenal (HPI, equivalent to mammalian hypothalamus-pituitary-adrenal) axis was likely involved. This activation, probably not related to the control of food intake through FA sensor systems but to the modulation of lipolysis in peripheral tissues, liver and Brockmann b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…If insulin treatment enhances FA-sensing response in hypothalamus, a strong inhibitory signal would therefore arrive to the liver resulting in a potentiation of the responses elicited by FA alone. In BB, we had previously reported that FA-sensing systems present in this tissue respond directly to changes in circulating levels of OL and OCT [8,10,12] although they could be influenced by endocrine systems such as insulin and previous hypothalamic FA sensing [14,15]. In the present study, we obtained information regarding the modulatory action of insulin on FA-sensing response in BB.…”
Section: Insulin Treatment Differentially Modified the Fa-sensing Resmentioning
confidence: 77%
See 3 more Smart Citations
“…If insulin treatment enhances FA-sensing response in hypothalamus, a strong inhibitory signal would therefore arrive to the liver resulting in a potentiation of the responses elicited by FA alone. In BB, we had previously reported that FA-sensing systems present in this tissue respond directly to changes in circulating levels of OL and OCT [8,10,12] although they could be influenced by endocrine systems such as insulin and previous hypothalamic FA sensing [14,15]. In the present study, we obtained information regarding the modulatory action of insulin on FA-sensing response in BB.…”
Section: Insulin Treatment Differentially Modified the Fa-sensing Resmentioning
confidence: 77%
“…We also evaluated in hypothalamus, liver, and BB concentrations of FA, triglyceride, total lipid, glucose, and glycogen (only in liver), as well as variables related to putative FA-sensing systems based on (1) FA metabolism, such as activities of fatty acid synthase (FAS), malonyl-CoA decarboxylase activity (MCD; only in liver), ATPcitrate lyase (ACLY; only in hypothalamus), and CPT-1, and mRNA abundance of acetyl-CoA carboxylase (ACC; only in hypothalamus), ACLY, CPT-1a (in BB), CPT-1b (in BB), CPT-1c (hypothalamus), and FAS; (2) binding to FAT/CD36 and further modulation of transcription factors, such as mRNA abundance of FAT/CD36, PPARa, SREBP1c, and liver X receptor a (LXRa); and (3) mitochondrial activity, such as mRNA abundance of mitochondrial uncoupling protein 2a (UCP2a), hydroxyacyl-CoA dehydrogenase (HOAD), inward rectifier K þ channel pore type 6.x-like (Kir6.x-like), and sulfonylurea receptor-like (SUR-like; only in liver). These variables have been previously reported to change in the same species in response to increased levels of OL or OCT [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A similar experimental approach in rainbow trout also resulted in the inhibition of fatty acid sensing systems in hypothalamus, BB, and liver, and these changes apparently relate to the activation of hypothalamus-pituitary-interrenal (HPI) axis (Librán-Pérez et al, 2014b, 2015d). …”
Section: Nutrient Sensing Mechanisms In Fishmentioning
confidence: 99%